(untitled) (Journal of Biomedical Investigation, 2025)
Background: Cervical cancer is the second most common cause of death from cancer among women in Nigeria. Most studies indicate that the level of knowledge of cervical cancer and its preventive measures are low among the women population. Aim: To assess the level of Knowledge, Attitude, Practice and Acceptability of cervical cancer screening among women in FCT, Abuja. Materials and methods: A cross-sectional descriptive study design was used and data were collected from respondents using self-administered structured questionnaire. Data were collected from three hundred and fifty-seven (357) respondents whose ages ranged from 20 to 60+ years. Data was presented using descriptive statistics of frequency distribution tables and charts, while chi-square was used to determine associations at the <0.05 level of significance. Results: The result showed that the women had a good knowledge (90.0%) and a positive attitude (90.0%) with a poor practice (44.0%) of cervical cancer screening. The acceptability among the women was reasonably good (60.0%) and the most preventive measure against cervical cancer infection was Human Papilloma Virus vaccination before sexual debut (98.0%, p=0.001), followed by regular PAP smear test (92.0, p=0.003). Fear of diagnosis (p=0.032), embarrassment (p=0.021), financial constraints (p=0.001), stigma (p=0.001) and staff attitude (p=0.036) were the barriers to cervical cancer screening among the study population. Conclusion: The study revealed that the women had a good knowledge of cervical cancer screening, and positive attitude towards cervical cancer screening. However, a poor practice of cervical cancer screening was observed among the women, therefore, there is need for enlightenment campaign towards increasing the involvement of more women in participating in the cervical cancer screening programmes that will enable and encourage them to participate more in the screening exercises.